Keberagaman jenis jamur makroskopis di kawasan wisata sumber ubalan Kediri - Farida Nurlaila Zunaidah; Tutut Indah Sulistiyowati (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2020)
The data collection of mushroom species found in Ubalan source tourism areas needs to be done as a source of data on the diversity of mushroom species as decomposers of organic material. This type of research is a descriptive exploratory study with methods. roaming modified with VES (Visual Encounter Survey). The research instrument used was a logbook, observation sheet, and the key book of determination. All mushrooms were collected in a collection bottle and identified by using a macro mushroom determination key in the Botany Laboratory of the Nusantara University PGRI Kediri. The data of this research are the types of macroscopic fungi found during observation. The data analysis technique used is descriptive qualitative. The results showed that there were twelveidentified fungal families, namely Auriculariae, Tricholomataceae, Ganodermataceae, Amanitaceae, Hymenogastraceae, Marasmiaceae, Russulaceae, Agaricaceae, Amanithaceae, Mycenaceae, Polyporaceae and Parmeliaceae. The conclusions of this study indicate that the area of the tourist area of the Ubalan has a variety of macroscopic fungi.